Turning Hype into Intention: FoMO Mediated Effects of TikTok Influence on Sustainable Buying - Agustino, Clarissa Belinda; Trisnawati, Juliani Dyah; Kusumawardhany, Prita Ayu (Dinasti Publisher, 2025)
This study explores how TikTok influences turn social-media buzz into intentions to buy sustainable products among Indonesian Generation Z consumers. It investigates both the direct and indirect impacts of TikTok influence on sustainable purchase intention, with Fear of Missing Out (FoMO) and sustainable attitudes acting as mediators. The research involved an online survey of 250 active TikTok users aged 17 to 25 who had previously bought eco-friendly products. Data were analyzed using structural equation modelling with partial least squares (SEM-PLS). The findings show that TikTok positively and significantly affects sustainable purchase intentions. Furthermore, TikTok influence boosts FoMO and strengthens positive attitudes toward eco-friendly products, and these factors further encourage sustainable purchasing intentions. The results indicate that social pressure to keep up with TikTok trends, alongside positive perceptions of sustainable products, plays a key role in turning social media excitement into actual sustainable purchase decisions. This study offers practical insights for marketers and policymakers on creating responsible TikTok content to support sustainable consumption.